“Sympathy” vs.“Empathy”: Comparing experiences of I2Audits and disability simulations - Hicks, Emily C.; Traci, Meg A.; Korb, Karin (Frontiers in Rehabilitation Sciences, 2022)
People with disability often experience stigma and discrimination, and people with disability in rural areas may experience these at higher rates. Additionally, people with disability in rural areas may have fewer opportunities for physical and social participation due to barriers in the built environment. Activities such as disability simulations and inclusive, interdisciplinary community planning workshops (i.e., I2Audits) seek to draw awareness to and address these problematic experiences. The present study used thematic analysis from qualitative research to examine the advantages and disadvantages of using disability simulations and I2Audits in rural communities. Findings suggest that disability simulations increase stigmatization, lead to feelings of embarrassment and discomfort, and do not capture the experiences of people with disability. On the other hand, I2Audits lead to meaningful environmental changes, create feelings of empowerment, and center the lived experiences of people with disability within a bio-psycho-social model of disability. Results suggest that not only can I2Audits be a powerful tool to draw attention to physical barriers that people with disability face, but they also draw attention to the multi-level changes needed to increase opportunities for participation and address sources of stigma and discrimination in rural areas.